Medium Voltage Electrical Stimulation and Aging Enhance Meat Quality in Crossbred Bulls - Oliveira, Camila P. [UNESP]; Baldassini, Welder A. [UNESP]; Chardulo, Luis Artur [UNESP]; Coutinho, Marcelo; Rovadoscki, Gregori; Torrecilhas, Juliana A. [UNESP]; Pereira, Guilherme L. [UNESP]; Curi, Rogério A. [UNESP]; Torres, Rodrigo N. S. [UNESP]; Machado Neto, Otávio R. [UNESP] (Springer Nature, 2024)
The combination of post-slaughter and post-mortem technologies offers a strategy to enhance beef quality. In this study, carcass medium-voltage electrical stimulation — MVES (120 V, 60 Hz, 5 A) and aging were evaluated on both objective and sensory meat quality parameters in crossbred bulls. Sixty carcasses of F1 Angus × Nellore bulls were used. The MVES was applied pre chilling for 10 s to the cranial region of the left half-carcass of each animal, while the right half-carcass did not receive electrical stimuli (control). After 48 h of chilling, Longissimus thoracis samples (12–13th ribs; cranial direction) were collected and aged 14 and 21 days for fresh meat color assessment (L*, a*, b*, C*, and h*), purge losses, Warner–Bratzler shear force (WBSF) and cook loss. A sensory test with untrained consumers (n = 138) was conducted to assess tenderness (TE), flavor (FL), juiciness (JU), and overall acceptance (OA). Interaction (P < 0.05) between MVES and aging was observed for meat color variables such as b* and C*. Meat samples presented higher b* and C* values (P < 0.05) using MVES and aging compared to control at 21 days of aging (b* = 6.81 vs. 6.07 ± 0.14; and C* = 16.19 vs. 14.85 ± 0.51), while purge and cooking losses remained unaffected (P > 0.05). Additionally, there was a reduction (P < 0.05) in WBSF in response to MVES at 21 days of aging (4.41 vs. 3.92 ± 0.10 kg). Although carcass MVES did not influence (P > 0.05) eating quality of meat (TE, FL, JU and OA), the combination with aging enhanced meat color in crossbred bulls. Besides, MVES reduced WBSF values after 21 days of aging, indicating improved objective tenderness despite the lack of impact on sensory evaluations.
Keywords: Bos indicus; Bos taurus; Carcass; Feedlot; Meat color; Tenderness